Shallow groundwater in the Atankwidi Catchment of the White Volta Basin: current status and future sustainability - Barry, Boubacar; Kortatsi, B.; Forkuor, Gerald; Gumma, Murali K.; Namara, Regassa E.; Rebelo, Lisa-Maria; Berg, J. van den; Laube, W. (International Water Management Institute, 2010)
The Atankwidi Catchment, which lies in the White Volta Basin in West Africa, is intensively cultivated by locals for economic gains. During dry seasons, farmers irrigate their crops, chiefly tomatoes, using shallow groundwater harvested from shallow ponds they dig using simple tools like an axe, hoe, bucket and bowls. Recent expansion in cultivated areas has brought to the fore the need to estimate the volume of shallow groundwater stored in the catchment?s underlying aquifer and to what extent it can sustain the incremental growth in irrigated areas.